INFORMATION SYSTEM DESIGN AND INVENTORY MANAGEMENT ON PHARMACY BUSINESS WITHIN ABC-XYZ ANALYSIS METHOD - Christopher Amadeus Herlambang; Joniarto Parung (Universitas Airlangga, 2021)
Inventory will difficult to be controlled when there is an increase on product item number. It needs product grouping analysis to determine product priorities. So that, an inventory management information system that supports inventory planning process becomes important to discuss. The same problem is also experienced by Kutisari pharmacy which has nearly 1500 product items that controlled by conventional-based stock and inventory recording system. Based on observations pharmacy planning is currently done based on the owner subjectivity. The expired goods is often became problem because control system is still conventional and number of product items is quite large. Researchers classify products in various stages with final result being a combination of ABC and XYZ classifications. The demand data for priority products is forecasted according to the model that gives best MAPE/MSD results and researcher improves inventory management system flow by implementing an inventory management information system at Kutisari Pharmacy. After that, an analysis is carried out to find out benefits of application system. Based on data analysis, losses from expired drugs and goods that are not recorded in warehouse resulted in lost sales of Rp. 3,312,000 in a year. In future this losses could be prevented and minimized, so that it can be benefits for pharmacy business.